KELEMBAGAAN DAN STRATEGI PENINGKATAN DAYA SAING KOMODITAS CABAI KAPUPATEN GARUT - Silmi Tsurayya; Lindawati Kartika (Jurnal Manajemen & Agribisnis, 2015)
The objectives of this study were to identify supply chains, analyze the institutions, formulate strategies for competitiveness enhancement, design competitiveness enhancement model, and determine the main strategies in competitiveness enhancement of chili pepper in Garut District. This study used primary data (observations, interviews, and questionnaires) and secondary data (literature study). The data were processed and analyzed by Descriptive Analysis, SWOT Analysis, the House Model, and Pairwise Comparison. The results of this study showed that: 1) there were 6 supply chain structures in chili pepper distribution; 2) the major institutional sectors contributed to competitiveness enhancement of chili pepper including public sector, voluntary sector, and private sector; 3) SWOT Analysis obtained 15 alternative strategies; 4) the House Model as competitiveness enhancement model had 3 pillars consisting of products, human resource, and institutional and marketing; 5) the main strategies in competitiveness enhancement of chili pepper included Increase in the number of productions, Market expansion, and Partnership Strengthening and development. The managerial implications of the study suggest: 1) land expansion and plant arrangement pattern to ensure continuity of production quantities; 2) Optimization of the role of Agribusiness Sub-Terminal as the marketing institution; and 3) Maximization in the government’s role in facilitating farmer groups with associations or corporations.Keywords: institutional, the house model, competitiveness, chili, SWOTABSTRAKPenelitian ini bertujuan mengidentifikasi rantai pasok, menganalisis kelembagaan, merumuskan strategi peningkatan daya saing, merancang model peningkatan daya saing, dan menentukan strategi utama dalam peningkatan daya saing  komoditas cabai di Kabupaten Garut. Data yang digunakan terdiri dari data primer (observasi, wawancara, dan kuesioner) dan data sekunder (studi literatur). Metode pengolahan dan analisis data yang digunakan adalah analisis deskriptif, analisis SWOT, The House Model dan Pairwise Comparison. Hasil penelitian menunjukkan bahwa: 1) Terdapat enam struktur rantai pasok dalam pendistribusian komoditas cabai; 2) Sektor utama kelembagaan yang berperan dalam peningkatan daya saing komoditas cabai adalah public sector, voluntary sector, dan private sector; 3) Analisis SWOT menghasilkan 15 alternatif strategi; 4) The House Model sebagai model peningkatan daya saing memiliki tiga pilar utama yang berkaitan dengan produk; sumber daya manusia; kelembagaan dan pemasaran;  5) Strategi utama dalam peningkatan daya saing komoditas cabai adalah peningkatan jumlah produksi; perluasan pangsa pasar; dan penguatan dan pengembangan kemitraan. Implikasi manajerial hasil penelitian merekomendasikan: 1) perluasan lahan dan pengaturan pola tanam untuk menjamin kontinuitas jumlah produksi; 2) mengoptimalkan peran subterminal agribisnis sebagai lembaga pemasaran; 3) memaksimalkan peran pemerintah dalam memfasilitasi kelompok tani dengan asosiasi atau perusahaan.Kata kunci: kelembagaan, the house model, daya saing, cabai, SWOT